Buße in der Alten Kirche - Volp, Ulrich (Studien der Patristischen Arbeitsgemeinschaft, 2023)
103864_VOLP_SPA17_00_OM -- 103864_VOLP_SPA17_00_VW -- 103864_VOLP_SPA17_01_Volp -- 103864_VOLP_SPA17_02_Frenschkowski -- 103864_VOLP_SPA17_03_Buchinger -- 103864_VOLP_SPA17_04_Kingreen -- 103864_VOLP_SPA17_05_Gemeinhardt -- 103864_VOLP_SPA17_06_Winnebeck -- 103864_VOLP_SPA17_07_Autorinnen-und-Autoren -- 103864_VOLP_SPA17_08_Index.